DESIGN STANDARD OPERATING PROCEDURE ESD (ELECTROSTATIC DISCHARGE) APPLICATION IN DEPT. PEGATRON AT PT.SAT NUSAPERSADA TBK - Erwin Yoe; ing Sabariman (ConCEPt - Conference on Community Engagement Project, 2022)
This internship aims to overcome the problems at PT Sat Nusapersada in the need for employees to follow ESD procedures in the manufacturing industry because of their lack of education in ESD procedures. Internship activities are carried out during the period 15 March 2021 till 15 September 2021. The method used in the implementation of this internship is observation, design, and implementation.This internship resulted in a documented internal application for the company. The outputs submitted to the company include data on company assets, employee liabilities, and company profiles. The supporting documents include a questionnaire on the use of internal applications within the company. The SOP application for ESD is designed using HTML and CSS programming languages. This application is designed starting from an easy-to-use interface and the availability of the material in the form of videos, PDFs, and PowerPoint. This application design has been successful and can display the appropriate design. This application has also been used in several areas within the Pegatron department at PT Sat Nusapersada as an application to make it easier to find information about ESD.